An POTENSI PEMANFAATAN AREA KOSONG PADA BANGUNAN RAILINK GUNA MENDUKUNG PENDAPATAN NON AERONAUTICAL DI BANDARA INTERNASIONAL KUALANAMU - Nabila Inayah; Agoes Soebagio; Rini Sadiatmi (FTK UNSURYA, 2026)
Kualanamu International Airport still relies on aeronautical revenue of 80%, while non-aeronautical contributions are only 20%. This condition requires diversification of revenue sources, especially after the COVID-19 pandemic. This research aims to analyze strategies for utilizing vacant areas in Railink buildings to increase non-aeronautical revenue. The method used is a descriptive qualitative approach through observation, interviews with commercial unit managers and documentation. Data analysis was conducted using the value proposition canvas business model. The results showed that the vacant area is feasible to develop as a Commercial Lifestyle Hub that includes a children’s playground and event spaces. The potential contribution from this development is estimated to increase non-aeronautical revenue by 35-40% in five years. Key strategies include digital promotion, local collaboration and direct marketing. This optimization of non-productive assets not only strengthens the airport's financial stability, but also supports local economic growth and long-term competitiveness.